1990
DOI: 10.1128/jvi.64.11.5688-5693.1990
|View full text |Cite
|
Sign up to set email alerts
|

Open reading frame vpr of simian immunodeficiency virus encodes a virion-associated protein

Abstract: The genomes of simian immunodeficiency viruses isolated from rhesus macaques (SIVmac) contain an open reading frame (ORF), vpr, which has a coding potential of 97 to 101 amino acid residues. In this study, a vpr ORF-encoded protein of approximately 11 kDa was identified, and anti-vpr antibodies were detected in rhesus macaques infected by SlVmac. These results provide clear evidence that the vpr ORF is a coding gene of SIVmac The vpr protein, like the vpx protein which is encoded by another accessory gene of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 42 publications
3
38
0
1
Order By: Relevance
“…Vpr and Vpx were shown to be present in viral particles as a result of specific interactions with the Gag polypeptides (4,14,22,28,39,41,43). The presence of HIV-1 Vpr and the matrix protein in virions appears to determine nuclear transport of the preintegration complex in nondividing cells (2,11,13).…”
Section: Induction Of G 2 Arrest Is a General Function Of Vpr From DImentioning
confidence: 99%
“…Vpr and Vpx were shown to be present in viral particles as a result of specific interactions with the Gag polypeptides (4,14,22,28,39,41,43). The presence of HIV-1 Vpr and the matrix protein in virions appears to determine nuclear transport of the preintegration complex in nondividing cells (2,11,13).…”
Section: Induction Of G 2 Arrest Is a General Function Of Vpr From DImentioning
confidence: 99%
“…An amphipathic helix near the N-terminus of Vpr has been implicated in the virion incorporation (Mahalingam et al, 1995a,b). Because of its virion association, it has been suggested that Vpr has an early role in HIV-1 infection, possibly in penetration or uncoating of the virus (Cohen etal., 1990a;Yuan et al, 1990;Yu et al, 1990), or in the nuclear transport of the pre-integration complex (Heinzinger et a/., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This 96-amino-acid protein is an important factor for the pathogenesis of HIV [1,2]. Vpr is an integral part of viral particles suggesting an important role in early stages of infection [3][4][5][6]. Vpr is involved in the transport of the preintegration complex into the host cell nucleus, which is an important feature for infection of nondividing cells [7,8].…”
mentioning
confidence: 99%